True Stories of History and Biography - Hawthorne, Nathaniel, 1804-1864 (Salt Lake City, UT : Project Gutenberg, 2005)
"True Stories from History and Biography" by Nathaniel Hawthorne is a collection of historical narratives and biographical sketches intended for a younger audience, written in the mid-19th century. The work aims to introduce young readers to significant historical figures and events in American history through engaging storytelling. The narrative begins with a whimsical premise: an old chair, presumably containing a rich history, serves as the focal point around which tales are spun, allowing readers to explore the lives of important Puritan characters and the early settlers of New England. At the start of the book, we are introduced to the character of Grandfather, who engages a group of children, particularly a curious young girl named Alice, with stories derived from the past. He describes how his old chair has a storied history, having been used by notable figures like Lady Arbella and Governor Winthrop among others. Grandfather's narratives cover the early Puritan settlers, their struggles, and their pursuit of religious freedom, connecting the chair's history to the founding of the New England colonies. Through his tales, he not only recounts historical events but also infuses them with reflections on the nature of life, family, and the passing of generations, setting the stage for a captivating historical journey. (This is an automatically generated summary.)
The whole history of grandfather's chair. Complete in three parts -- Biographical stories: Benjamin West. Sir Isaac Newton. Samuel Johnson. Oliver Cromwell. Benjamin Franklin. Queen Christina.
Release date is 2005-04-24
Keywords: Biography -- Juvenile literature; Massachusetts -- History -- Juvenile literature; Massachusetts -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature